Caffey disease in neonatal period: the importance of the family!. (9th October 2012) - Prior, Ana Rita; Moldovan, Oana; Azevedo, António; Moniz, Carlos
Abstract : A male newborn was apparently well until his second day of life, when increased irritability and a swelling in his right leg were noted. He was rooming-in with his mother since birth. On examination, a mass on the anterior surface of the right leg was noticed. The mass was firm, elongated, ill-defined, unmovable and painful at palpation. No overlying skin changes were seen. The newborn had a family history of neonatal bone swelling with resolution before the age of 2. Subsequent images showed hyperostosis in the diaphysis of the right tibia. After exclusion of other conditions such as trauma, osteomyelitis and congenital syphilis, the involvement of the tibial diaphysis, sparing the epiphyses and the benign course of the disease in family history, were indicative of Caffey disease. The genetic study confirmed this diagnosis. Caffey disease, although rare, should not be overlooked in the diagnostic approach to childhood bone swelling.